Trimethylamine-N-oxide (TMAO) mediates the crosstalk between the gut microbiota and hepatic vascular niche to alleviate liver fibrosis in nonalcoholic steatohepatitis - Zhou, Dengcheng; Zhang, Jing; Xiao, Chengju; Mo, Chunheng; Ding, Bi-Sen (Frontiers in Immunology, 2022)
Liver fibrosis is one main histological characteristic of nonalcoholic steatohepatitis (NASH), a disease paralleling a worldwide surge in metabolic syndromes with no approved therapies. The role of the gut microbiota in NASH pathogenesis has not been thoroughly illustrated, especially how the gut microbiota derives metabolites to influence the distal liver in NASH. Here, we performed 16S rDNA amplicon sequencing analysis of feces from a mouse NASH model induced by a Western diet and CCl4 injury and found genera under Streptococcaceae, Slcaligenaceae, Sscillibacter, and Sseudochrobactrum, which are related metabolites of trimethylamine-N-oxide (TMAO). Injection of the gut microbial metabolite TMAO reduced the progression of liver fibrosis in the mouse NASH model. Further analysis revealed that the anti-fibrotic TMAO normalized gut microbiota diversity and preserved liver sinusoidal endothelial cell integrity by inhibiting endothelial beta 1-subunit of Na (+), K (+)-ATPase (ATP1B1) expression. Collectively, our findings suggest TMAO-mediated crosstalk between microbiota metabolites and hepatic vasculature, and perturbation of this crosstalk disrupts sinusoidal vasculature to promote liver fibrosis in NASH.